The Impact of Budget Time Pressure on Professional Conduct During the Covid-19 Period - Fia Fauzia Burhanuddin; Gagaring Pagalung; Andi Kusumawati (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study aims to examine the effect of professionalism and time budget pressure on audit quality, with job stress as a moderating variable during the COVID-19 pandemic. Method - This research employs a quantitative explanatory approach using a survey method, with data collected via questionnaires distributed to auditors at the BPK RI South Sulawesi Representative Office. The analysis was conducted using Structural Equation Modeling (SEM) through SmartPLS to test the relationships and moderating effects among variables. Main Findings - The study finds that time budget pressure negatively affects audit quality, while professionalism has a positive effect. Job stress significantly moderates both the relationship between time budget pressure and audit quality and the relationship between professionalism and audit quality. These findings suggest that psychological stress during the pandemic amplifies the impact of professional behavior and time constraints on audit outcomes. Theory and Practical Implications - This study strengthens the Job Demands-Resources and Attribution Theory by demonstrating that job stress significantly moderates the relationship between time budget pressure and professionalism on audit quality, especially in crisis contexts such as the COVID-19 pandemic. Practically, the findings highlight the need for audit institutions to manage auditor workload and stress levels effectively to maintain high audit quality during disruptive periods Novelty - This study offers novelty by introducing job stress as a moderating variable in the relationship between time budget pressure and professionalism on audit quality during the COVID-19 pandemic, which has rarely been explored in previous literature.